Kaonic atoms measurements with SIDDHARTA-2. Issue 1 (1st February 2023) - Sgaramella, F.; Bazzi, M.; Bosnar, D.; Bragadireanu, M.; Cargnelli, M.; Carminati, M.; Clozza, A.; Deda, G.; Del Grande, R.; De Paolis, L.; Dulski, K.; Fabbietti, L.; et al.
Abstract: The SIDDHARTA-2 collaboration is aiming to perform the challenging measurement of kaonic deuterium X-ray transitions to the ground state. This will allow to extract the isospin-dependent antikaon-nucleon scattering lengths, providing input to the theory of Quantum Chromodynamics (QCD) in the non-perturbative regime with strangeness. This work describes the SIDDHARTA-2 experimental apparatus and presents the results obtained during the commissioning phase realized with kaonic helium measurements. In particular, the first observation of the kaonic helium transitions to the 3s level (M-lines), reported in this work, represents a new source of information to study the kaonic helium cascade process and demonstrates the potential of the SIDDHARTA-2 apparatus, in the view of the ambitious kaonic deuterium measurement.